2021
DOI: 10.1002/er.7022
|View full text |Cite
|
Sign up to set email alerts
|

New lead‐free double perovskites X 2 GeI 6 (X = K, Rb, Cs) for solar cells, and renewable energy as an alternate of hybrid perovskites

Abstract: Summary Recently, the unique double perovskites are continuously being used for solar cells and thermoelectric applications because of stable structures and high energy conversion efficiency. We addressed the optical and transport characteristics of X2GeI6 (X = K, Rb, Cs) by first‐principle calculations. The tolerance factor confirms the structural stability. The computed band gaps 1.27 eV (K2GeI6), 1.24 eV (Rb2GeI6), and 1.13 eV (Cs2GeI6) plunge the maximum absorption in visible light zone. The first absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 51 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Mahmood et al [ 22 ] investigated perovskites material Rb 2 Pd(Cl/Br) 6 by using the DFT approach and found that the energy gap of the system is reduced from 1.88 to 1.21 eV when Cl is replaced by Br anion. Al‐Muhimeed et al [ 23 ] investigated X 2 GeI 6 (X = K, Rb, Cs) by using a computational technique. They reported the band gap of K 2 GeI 6 , Rb 2 GeI 6 , and Cs 2 GeI 6 as 1.27, 1.24, and 1.13 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmood et al [ 22 ] investigated perovskites material Rb 2 Pd(Cl/Br) 6 by using the DFT approach and found that the energy gap of the system is reduced from 1.88 to 1.21 eV when Cl is replaced by Br anion. Al‐Muhimeed et al [ 23 ] investigated X 2 GeI 6 (X = K, Rb, Cs) by using a computational technique. They reported the band gap of K 2 GeI 6 , Rb 2 GeI 6 , and Cs 2 GeI 6 as 1.27, 1.24, and 1.13 eV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Rb 2 PdI 6 , with an energy gap of 0.92 eV and high optical absorption, is reported as a suitable material for photovoltaic devices. Al‐Muhimeed et al 30 studied X 2 GeI 6 (X = K, Rb, Cs) by using the DFT approach. They reported that the band gap, optical characteristics, and tolerance factor of these materials are in a suitable range and can be utilized for photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The extensive interest of researchers in double perovskites has grown over the last few years due to their conceivable implementation in renewable energy. 13,14 By using these perovskites the ongoing record power conversion efficiency reaches up to 25.7%. 15…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The extensive interest of researchers in double perovskites has grown over the last few years due to their conceivable implementation in renewable energy. 13,14 By using these perovskites the ongoing record power conversion efficiency reaches up to 25.7%. 15 For analyzing the most competent, reliable, and harmless substitutes, the double perovskites based on halide (X) (generally named as A 2 BB ′ X 6 ) have been searched.…”
Section: Introductionmentioning
confidence: 99%